1984
DOI: 10.4141/cjas84-140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lignosulfonate on Rumen Microbial Degradation of Soybean Meal Protein in Continuous Culture

Abstract: Degradation of protein by rumen microbes maintained in continuous culture was reduced when soybean meal was pelleted with calcium lignosulfonate. Ammonia nitrogen concentration in fermenter effluent decreased with lignosulfonate treatment which was consistent with an observed decrease in true organic matter digestion, volatile fatty acid production and cellulose digestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…Veen (1986) speculated that slowly fermented proteins and the resultant eradual release of ammonia-N, peptides and branched chain finy acids, promoted the availability of these essential growth factori to cellulolytic bacteria for an extended period of time after feeding. In contrast to our results, others have reoorted a decrease in fiber digestibility when SM in corn-based diets was treated with LSO3, and attributed this to a deficiency of ammonia-N for microbial protein synthesis (Windschitl and Stern 1988;Stern 1984). This apparent inconsistency may be due to our use of barley, which is more rapidly and efficiently colonized by rumen microbes ihun i, .o.n (McAllister et al 1990b) resulting in a more rapid digestion of barley protein and higher production of ammonia with barley-based than corn-based diets.…”
contrasting
confidence: 54%
“…Veen (1986) speculated that slowly fermented proteins and the resultant eradual release of ammonia-N, peptides and branched chain finy acids, promoted the availability of these essential growth factori to cellulolytic bacteria for an extended period of time after feeding. In contrast to our results, others have reoorted a decrease in fiber digestibility when SM in corn-based diets was treated with LSO3, and attributed this to a deficiency of ammonia-N for microbial protein synthesis (Windschitl and Stern 1988;Stern 1984). This apparent inconsistency may be due to our use of barley, which is more rapidly and efficiently colonized by rumen microbes ihun i, .o.n (McAllister et al 1990b) resulting in a more rapid digestion of barley protein and higher production of ammonia with barley-based than corn-based diets.…”
contrasting
confidence: 54%
“…Moreover, they appeared to reflect increased apparent digestibilities of the NDF and ADF components of the diets supplemented with LSO 3 CM compared with the other 2 treatments. This finding of increased apparent digestibility of NDF and ADF for diets supplemented with LSO 3 CM compared with those supplemented with UCM or HTCM indicated that the ammonia N levels were not limiting fiber digestion as they were in the previous studies of Stern (1984) and Windschitl and Stern (1988b). The increase in fecal N losses for cows fed the LSO 3 CM supplement reflected the lower protein degradability associated with feeding that supplement.…”
Section: Discussionmentioning
confidence: 55%
“…The most commonly used process to protect soybean protein involves the application of heat, either directly or in the process of pelleting or extrusion. Heat treatment of soybean meal (SBM) reduces crude protein (CP) solubility and rumen ammonia levels (Tagari et al 1962), reduces rumen in situ nitrogen (N) degradation and augments flow of dietary amino acids to the small intestine (Glimp et al 1967 (Stern 1984;Cleale et al l987a,b). Furrhermore, whole blood from slaughter houses is a reusable by-product due to a high protein content as well as low rumen degradability when heated (Orskov et al 1980;Loerch et al 1983).…”
mentioning
confidence: 99%